Rheology-dependent magma reservoir pressurization history constrained by the deformation cycle of Okmok volcano, Alaska - Jared M. Long-Fox; Sui Tung; Theodore Donovan; Timothy Masterlark (Frontiers in Earth Science)
The eruption cycle of a volcano is controlled by the subsurface migration and storage of magma. The specific characteristics of the magma migration and spatial distribution of material properties produce a specific deformation signature on the Earth’s surface. Inverse analyses of geodetic data are used to optimize characteristic geometric and mechanical parameters of the volcanic system and hence provide information on the subsurface magmatic system. This study uses interferometric synthetic aperture radar data from a 1997 co- and post-eruptive interval for Okmok volcano to estimate the location of the magma reservoir and constrain finite element-based viscosity models of a thermally-weakened viscoelastic rind surrounding the reservoir. For the first time, approximately 10 years of pre-and post-eruption interferometric synthetic aperture radar data are analyzed to recover a magma reservoir pressurization history using both purely elastic and coupled elastic-viscoelastic models. The findings show that low viscosities surrounding the magma reservoir relax stresses rapidly enough to allow prediction of the more realistic viscoelastic pressurization histories to be calculated as a scaled version of the relatively simple but computationally efficient elastic models which allows for quick analysis of volcano hazards while maintaining fidelity to the actual physical system. This offers insights into how the shallow rheologic structure of magmatic systems can influence the predictions of transient deformation and estimates of the time-dependent magma budget.